The effect of the generative learning strategy on the achievement of students of the Department of Art Education in the subject of school theater (Journal of the College of Basic Education, 2022)
The current study aims to identify the impact of the generative learning strategy on the achievement of students of the Department of Art Education in the subject of school theater, as the first chapter dealt with the research problem, its importance and the aim of the study. The experimental group consisted of two groups (experimental and control), as the research community consisted of students of the Department of Art Education in the College of Basic Education, Al-Mustansiriya University, the second stage, numbering 206 students. Honestly and reliability, as the researcher used the statistical bag (spss) as it is the most suitable for the current study, as it was shown that the experimental group who studied according to the generative learning strategy was superior to the students of the control group who studied in the usual way.